Identification of Australian Aboriginal and Torres Strait Islander Cancer Patients in the Primary Health Care Setting - Audra de Witt; Audra de Witt; Audra de Witt; Frances C. Cunningham; Frances C. Cunningham; Ross Bailie; Christina M. Bernardes; Christina M. Bernardes; Christina M. Bernardes; Veronica Matthews; Brian Arley; Brian Arley; et al. (Frontiers Media S.A., 2017)
BackgroundAboriginal and Torres Strait Islander Australians have poorer cancer outcomes and experience 30% higher mortality rates compared to non-Indigenous Australians. Primary health care (PHC) services are increasingly being recognized as pivotal in improving Indigenous cancer patient outcomes. It is currently unknown whether patient information systems and practices in PHC settings accurately record Indigenous and cancer status. Being able to identify Indigenous cancer patients accessing services in PHC settings is the first step in improving outcomes.MethodsAboriginal Medical Centres, mainstream (non-Indigenous specific), and government-operated centers in Queensland were contacted and data were collected by telephone during the period from 2014 to 2016. Participants were asked to (i) identify the number of patients diagnosed with cancer attending the service in the previous year; (ii) identify the Indigenous status of these patients and if this information was available; and (iii) advise how this information was obtained.ResultsTen primary health care centers (PHCCs) across Queensland participated in this study. Four centers were located in regional areas, three in remote areas and three in major cities. All participating centers reported ability to identify Indigenous cancer patients attending their service and utilizing electronic Patient Care Information Systems (PCIS) to manage their records; however, not all centers were able to identify Indigenous cancer patients in this way. Indigenous cancer patients were identified by PHCCs using PCIS (n = 8), searching paper records (n = 1), and combination of PCIS and staff recall (n = 1). Six different types of PCIS were being utilized by participating centers. There was no standardized way to identify Indigenous cancer patients across centers. Health service information systems, search functions and capacities of systems, and staff skill in extracting data using PCIS varied between centers.ConclusionIt is crucial to be able to easily identify Indigenous cancer patients accessing health services in the PHC setting to monitor progress, improve and evaluate care, and ultimately improve Indigenous cancer outcomes. It is also important for PHC staff to receive adequate training and support to utilize PCISs efficiently and effectively.